Emerging Role of Immunity in Cerebral Small Vessel Disease - Fu, Ying; Yan, Yaping (Frontiers in Immunology, 2018)
Cerebral small vessel disease (CSVD) is one of the main causes of vascular dementia in older individuals. Apart from risk containment, efforts to prevent or treat CSVD are ineffective due to their unknown pathogenesis. CSVD as a subtype of stroke is characterized by recurrent strokes and neurodegeneration. Impaired blood–brain barrier (BBB) intact, chronic inflammatory responses, and induced leukocyte infiltration are classical pathological features in CSVD. Understanding how disruption of BBB instigates and amplifies the inflammatory and degenerative responses may be instrumental in the design of novel treatments for CSVD. This review describes the neurovascular unit features of CSVD, immunity response on specific neuronal and glial processes that may be involved in a distinct mechanism of CSVD, and the current evidence on the association between mechanisms of inflammation and interventions in CSVD. We suggest that the autoimmune action should be assessed in future studies, which would benefit the development of effective therapeutic interventions in CSVD.